Exploring options to deepen and broaden the personal income tax base in South Africa - Gemma Clare Wright; Katrin Gasior; Joonas Ollonqvist; Wynnona Steyn; Winile Ngobeni; Helen Barnes; Michael Noble; David McLennan; Jukka Pirttilä; Ada Jansen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
In this paper we explore options for augmenting South Africa's personal income tax revenue using two microsimulation models: PITMOD simulates the personal income tax system and is underpinned by a dataset comprising a full extract of anonymized individual-level administrative tax data; and SAMOD simulates personal income tax and social benefits using a nationally representative survey. We explore policy reforms at both the upper and lower ends of the income distribution of tax-registered individuals and assess the impacts on revenue and measures of progressivity. The PITMOD simulations are enhanced by introducing a behavioural element to the model and are complemented by using SAMOD to estimate the impacts of the reforms on the whole population including those who are not tax-registered.
Keywords: C63; C81; D31; H24; 330; microsimulation; personal income tax; income distribution; South Africa